ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI YANG TERCATAT DI BEI (Studi kasus pada PT. Telekomunikasi Indonesia Tbk. dan PT. Indosat Tbk. periode 2006 – 2015) - Hafidzul Ulum; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThe increasingly tight business environment requires companies to have goodfinancial performance. Financial performance can be seen from the company'sfinancial statements in the previous period because it can as a reflection ofperformance for the next period with a certain calculation. This study aims todetermine the comparison of financial performance of PT TelekomunikasiIndonesiaTbk and PT Indosat Tbk from 2006 to 2015. The method used in thisstudy is qualitative data in the form of annual financial statements calculatedusing the curent ratio, debt to equity ratio, return on equity, return on Asset, netprofit margin, total asset turnover and economic value added (EVA). The resultsshow that the average value of the curent ratio, debt to equity ratio, return onequity, return on assets, net profit margin, and total asset turnover average valueof PT Telekomunikasi Indonesia Tbk better than PT Indosat Tbk. While theaverage value of economic value added (EVA) of PT Telekomunikasi IndonesiaTbk is better than PT Indosat Tbk.Keywords: Financial Ratios, Economic Value Added, Financial Performance